Familial rhabdoid tumour 'avant la lettre'—from pathology review to exome sequencing and back again. Issue 1 (6th August 2013) - Witkowski, Leora; Lalonde, Emilie; Zhang, Jian; Albrecht, Steffen; Hamel, Nancy; Cavallone, Luca; May, Sandra Thompson; Nicholson, James C; Coleman, Nicholas; Murray, Matthew J; Tauber, Peter F; Huntsman, David G; et al.
Abstract: Here we provide compelling evidence that next‐generation sequencing will revolutionize diagnostics. We reappraised a case from 1991, published in 1993, describing the unique occurrence of an ovarian immature teratoma arising in a young woman and a clonally distinct intracerebral immature teratoma developing in her daughter. We conducted whole‐exome sequencing on constitutional DNA from the mother and her daughter and identified a previously unreported nonsense mutation (c.3533G>A; p.Trp1178 * ) in the chromatin remodelling gene, SMARCA4, that was present in both individuals and was subject to nonsense‐mediated decay. Tumour analysis by Sanger sequencing revealed a somatic SMARCA4 mutation in both the mother (c.2438+1G>T) and her daughter (c.3229C>T; p.Arg1077 * ), which are predicted to be truncating. As immature teratomas are classified as germ cell tumours, we performed a comprehensive mutation survey of 106 apparently sporadic germ cell tumours, but did not find any other clearly deleterious SMARCA4 mutations. Recently, inactivating mutations in SMARCA4 have been found in two cases of rhabdoid tumour predisposition syndrome type 2. In the light of these findings, renewed efforts to locate previously unobtainable tumour samples were successfully undertaken. Histopathological and immunohistochemical re‐analysis of the daughter's tumour revealed that it was indeed a rhabdoid tumour (atypical teratoid/rhabdoid tumour). In this context, the original pathology report of the mother's ovarian tumour was re‐interpreted as describing a malignant rhabdoid tumour of the ovary. This report raises the question as to whether molecular genetic analysis should be included in tumour classification, alongside more traditional microscopy‐based methods. The use of new sequencing technologies, particularly when applied to archived samples, will lead to many more 'molecular rediagnoses'. This is the earliest known case of rhabdoid tumour predisposition syndrome type 2 and the first described case with an autosomal dominant pattern of inheritance, only discovered through an exome sequencing project. Copyright © 2013 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.